RETHINKING UNFAIR TRADING PRACTICES IN AGRICULTURE AND FOOD SUPPLY CHAIN: THE CROATIAN PERSPECTIVE (EU and comparative law issues and challenges series (ECLIC), 2021)
In recent years, the need for a systematic and harmonised way of preventing unfair trading practices (hereinafter UTPs) in the food supply chain has intensified at the European level due to many diverging national legislative solutions. These efforts resulted in the Directive 2019/633 on unfair trading practices (UTPs) in business-to-business relationships in the agricultural and food supply chain. Croatian UTPs Act, enacted already in 2017, was just amended to conform with the requirements of the named Directive. Generally speaking, the UTPs Act sets out rules and measures to prevent the imposition of UTPs in the food supply chain, establishes the list of such practices and sets up the enforcement structure and sanctions. Comparing the Directive to the UTPs Act, the authors discuss the outcome of the transposition pointing to the incorrect scope of application of the national legislation, its potential consequences and de lege ferenda solutions. Further, the authors anlyse the legal nature of the adopted UTPs system concluding that it does not fit into the traditional systematisation of laws jeopardising the coherency of the intricate and complex relationship between relating legislative frameworks. New rules are diverging and overlapping with both competition and contract law, leading to possible undesirable spill over effects in contract law, and unresolved concurring competence with competition law. Authors suggest precautionary interpretative measures as a means of solving the identified legal conundrum.